Gyülekezetépítés, de hogyan és milyen (m)értékek mentén? Egyes gyülekezetépítési modellek rövid áttekintése a 20. század közepétől a jelenkorig - KOCSEV, Miklós (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
Congregation Building, but how and According to What Standards/Values? A Brief Overview of Some Congregation Building Models from the Middle of the 20th Century to the Present Day Congregation building is one of the disciplines of practical theology. Its goal is to offer congregation models that are attractive and inspiring Christian congregations for today’s people. In this work, I review the models in the field of congregation building that I believe can meet this objective today.